Effects of ketogenic diet intervention on selected obese IIUM students during Ramadhan - Wan Ali Munawar, Wan Afiq Husaini; Amid, Azura; Abdullah, Aszrin (Food Research, 2020)
Obesity and overweight are one of the main problems faced by Malaysian society due to sedentary lifestyle and high-carbohydrate consumption. A “low glycemic diet” is suggested as a suitable alternative in preventing obesity, because of its low carbohydrate intake which can be referred to as Atkins or Ketogenic diet (KD). A case study was carried out to assess the effect of KD during Ramadan on obese individuals. KD meal intervention was developed upon consultation with a dietician and tailored for Sahur (a pre-dawn meal) and Iftar (evening meal for breaking fast). A total of six participants were involved in this study which consists of 2 groups. A control group of 3 selected obese male IIUM students received no specific diet, and a study group of 3 selected obese male IIUM students underwent KD meal intervention. The KD meal intervention was carried out one week before Ramadan to allow the participants’ body to familiarize with high fat and low carbohydrate diet. Results showed that most of the selected obese participants who applied KD meal intervention exhibited satisfactory results in weight and Body Mass Index (BMI) reduction, steady levels of blood glucose, normal blood pressure levels and the presence of ketone bodies at a p-value < 0.01. However, the participants in the control group showed no significant changes at p<0.01 in weight, BMI, blood glucose levels, blood pressure and not a trace of ketone bodies. The findings of this study indicated that KD showed a positive effect on obesity control when conducted during Ramadan fasting.